Reconciling Survey and Administrative Measures of Self-Employment - Abraham, Katharine G.; Haltiwanger, John C.; Hou, Claire; Sandusky, Kristin; Spletzer, James R. (Journal of Labor Economics, 2021)
Good information on self-employment is needed to inform the ongoing discussion of the rise of the gig economy and its implications for workers. Tax data show significant growth in self-employment not captured in the Annual Social and Economic Supplement to the Current Population Survey (CPS-ASEC). The growing gap reflects both self-employment in tax data missing from the CPS-ASEC and self-employment misreported as wage and salary work. We document consistent patterns in the discrepancies between the tax and survey data but are able to explain only a modest share of the growing disagreement between them.